If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -5 = 2(3 + -1x) Reorder the terms: -5 + X = 2(3 + -1x) -5 + X = (3 * 2 + -1x * 2) -5 + X = (6 + -2x) Solving -5 + X = 6 + -2x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + X = 6 + 5 + -2x Combine like terms: -5 + 5 = 0 0 + X = 6 + 5 + -2x X = 6 + 5 + -2x Combine like terms: 6 + 5 = 11 X = 11 + -2x Simplifying X = 11 + -2x
| (4x-8)-(7x+9)= | | x-4y=u | | 5=4m+4u | | 7x-35+14=7 | | (4/5)1.175= | | 3x-(5x-4)= | | 3p^4-18p^3-81p^2= | | 1+x-2x+3x-4x=0 | | 3x-4=2(X+5) | | .8x-.6x+.3x=3 | | 7x+8y+3=0 | | 3(a+b)-2(a-b)=0 | | (x)2.75x+71.48= | | -5(t-6)-(t+9)=2 | | 5x-9x=32 | | 8x-4=3x+1 | | 7m=2 | | -4x+4=-4 | | 2y+4=6y-6 | | 4350*.5= | | -20x^3+96x^2=0 | | -20x^3-96x^2=0 | | 9c*3=6 | | 49x^3-56x^2+16x=0 | | (5y^2-7y+3)+(-2y^2+4y+1)= | | 6p+4=2(2p+1) | | 10x+23(x-5)=182 | | 4(2x+1)=3(x+13) | | 12x^3+23x-24=0 | | 3.5b-33.4=75.5 | | 14p-10=8+2p | | 2g+14+5g=8-3+8 |